PENGARUH REKRUTMEN, SELEKSI, DAN PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN PT XYZ - KEZIA, ELGA; NURWANTI, NURWANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aims of this research was to define the effect of recruitment, selection, and employees placement on employee performance at PT XYZ. There was a research gap on employee performance which is related to recruitment, selection, and employee placement based on an interview with HR Team. Forms of this research was using descriptive and causality research. Using 80 sample of employees and the technique used is saturated sampling. Data analysis method used on this research is multiple linear regression. Data collected from questionnaire with likert scale used to measure. Proceeds of the research is recruitment and selection has no effect on employee performance but employee placement has an effect on employee performance.